APLIKASI TEKNOLOGI SEDERHANA DAN PERMESINAN UNTUK MENINGKATKAN KEAHLIAN RENOVASI LAMBUNG PERAHU - Seno Darmanto; Sutanto Sutanto; Sulaiman Sulaiman; Eko Julianto Sasono (IKIP PGRI Bojonegoro, 2018)
ABSTRACTApplications of technology and machinery equipment in service activities are done to complete the renovation and repair of boats or wooden vessels. Development of the infrastructure for members of the fishermen group is currently focused on equipment for the repair and renovation of the boat hull and the maintenance of the driving machine. And for the improvement of the renovation or repair of the boat hull, the service team has compiled a working activity including understanding and deepening of boat or wooden boats, engineering and equipment for renovation and boatbuilding, understanding and deepening of ship damage, and implementation in a group of fishermen. The process of maintenance and repair of boats on the ship's body (hull) in fishermen partners in principle were carried out through several stages include the washing and cleaning of all parts of the ship, patching, coating and painting. The process of painting through several stages of surface cleaning, patching if there are starting cracks and holes, drying, smoothing, basic coating and painting. Some tools for boats maintenance and repair especially for renovation and manufacture of wooden boats consist of saws (machines and manuals), drills, fittings, grinders, cutting (various sizes), clamps and other support equipmentKeywords: boat, hull, propulsion machine, machineryÂ ABSTRAKKegiatan pengabdian aplikasi teknologi dan peralatan permesinan dilakukan untuk menyempurnakan renovasi dan perbaikan perahu atau kapal kayu. Pengembangan kelengkapan sarana anggota kelompok nelayan pada saat ini difokuskan pada peralatan untuk perbaikan dan renovasi lambung atau bodi dan perawatan mesin penggerak. Dan untuk penyempurnaan renovasi atau perbaikan kapal kayu, tim pengabdian menyusun langkah kerja atau kegiatan pengabdian meliputi pemahaman dan pendalaman perahu atau kapal kayu, teknik dan peralatan renovasi dan pembuatan perahu, pemahaman dan pendalaman kerusakan kapal, dan sejenisnya dan pelaksanaan di kelompok nelayan. Proses perawatan dan perbaikan kapal pada bagian badan kapal (lambung kapal) di mitra nelayan pada prinsipnya dilakukan melalui beberapa tahapan meliputi pencucian seluruh bagian kapal, penambalan (pemakalan), pendempulan dan pengecetan kapal. Proses pengecatan melalui beberapa tahapan yakni pembersihan permukaan, penambalan kalau ada yang mulai retak dan berlubang, pengeringan, penghalusan, pelapisan dasar dan pengecatan.Â Beberapa peralatan perawatan dan perbaikan lambung perahu terutama untuk renovasi dan pembuatan perahu kayu meliputi gergaji kayu (mesin dan manual), bor, pasah, gerinda, tatah (berbagai ukuran), clem/pencepit dan peralatan pendukung lain.